Contemporary Topics in Patient Safety - Volume 1 2022
DOI: 10.5772/intechopen.95907
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Potential Risks with Fecal Microbiota Transplantation

Abstract: The therapeutic potential of Fecal Microbiota Transplantation (FMT) is greatly proved worldwide in the recent years. The use of FMT is now an accepted treatment modality and effective standard of care for some patients owing to its success in treating recurrent Clostridium Difficile Infection (rCDI). However, it is still evolving and longer term follow-up data regarding safety are required. Post-FMT serious adverse events (SAEs) have been varied between studies, however have included significant morbidity nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…MTT in a clinical trial has been reported to improve GI symptoms such as indigestion, abdominal pain, constipation, and diarrhea and symptoms related to ASD and normalized any alteration in the gut microbiota in ASD patients (D. W. Kang et al, 2017 , 2019 ). Thus, there is increasing interest in using FMT and MTT as a therapeutic intervention for treating children with NDDs, following all the concerning safety issues ( Gaonkar, 2021 ).…”
Section: Future Perspective On the Microbiome And Therapeutic Interve...mentioning
confidence: 99%
“…MTT in a clinical trial has been reported to improve GI symptoms such as indigestion, abdominal pain, constipation, and diarrhea and symptoms related to ASD and normalized any alteration in the gut microbiota in ASD patients (D. W. Kang et al, 2017 , 2019 ). Thus, there is increasing interest in using FMT and MTT as a therapeutic intervention for treating children with NDDs, following all the concerning safety issues ( Gaonkar, 2021 ).…”
Section: Future Perspective On the Microbiome And Therapeutic Interve...mentioning
confidence: 99%
“…In the context of the recent SARS-CoV-2 outbreak, stringent policies are required for the screening of FMT donors to ensure patient safety. In this concern, FDA directed that further safety measures are required for any investigational use of FMT, whether under an Investigational New Drug Application (IND) on file with the FDA or under FDA's enforcement discretion policy ( 78 ).…”
Section: Safety Concerns and Ethical Issues With Fmtmentioning
confidence: 99%